Cyber–Physiochemical Interfaces. Issue 8 (15th January 2020) - Wang, Ting; Wang, Ming; Yang, Le; Li, Zhuyun; Loh, Xian Jun; Chen, Xiaodong
Abstract: Living things rely on various physical, chemical, and biological interfaces, e.g., somatosensation, olfactory/gustatory perception, and nervous system response. They help organisms to perceive the world, adapt to their surroundings, and maintain internal and external balance. Interfacial information exchanges are complicated but efficient, delicate but precise, and multimodal but unisonous, which has driven researchers to study the science of such interfaces and develop techniques with potential applications in health monitoring, smart robotics, future wearable devices, and cyber physical/human systems. To understand better the issues in these interfaces, a cyber–physiochemical interface (CPI) that is capable of extracting biophysical and biochemical signals, and closely relating them to electronic, communication, and computing technology, to provide the core for aforementioned applications, is proposed. The scientific and technical progress in CPI is summarized, and the challenges to and strategies for building stable interfaces, including materials, sensor development, system integration, and data processing techniques are discussed. It is hoped that this will result in an unprecedented multi‐disciplinary network of scientific collaboration in CPI to explore much uncharted territory for progress, providing technical inspiration—to the development of the next‐generation personal healthcare technology, smart sports‐technology, adaptive prosthetics and augmentation of human capability, etc. Abstract : Cyber–physiochemical interfaces are presented and their issues including materials, sensor development, system‐level integration, and signal processing techniques are investigated. Such systems, properly optimized, can allow for the extraction of biophysical and biochemical signals, and sharing them with electronic and computing technology.